Analisis User Experience terhadap User Interface Website dengan Design Thinking: (Studi Kasus: Asuransi Online Superyou.co.id) - Nurliana, Friska; Hanifati, Ghassani; Ali, Ferdiansyah (Magenta | Official Journal STMK Trisakti, 2022)
The user interface is closely related to the user experience which is the key success of a website because a good design is not only aesthetic but also expected to be useful for its users. This study aims to analyze the user experience of the website’s user interface through design thinking so that can improve user understanding of the Superyou.co.id website. The research methodology is descriptive and qualitative in the form of written words from people and observed behavior with a human- centered approach through the stages of design thinking. Data was collected through interviews with users, company stakeholders, non-participant observation, and usability test in the 24-45 year age group as well as conducting a literature study. The study results show that users do not understand the information on the website both visually and content so they difficult to understand the purchase flow, causing disinterest and distrust of SuperYou.